Agrostis pendryi (Poaceae: Agrostidinae)—a new species from the Central Himalaya - Paszko, Beata (Phytotaxa, 2014)
Agrostis pendryi, a new species from Nepal and northwest India, is described and illustrated. This species is morphologically similar to A. pilosula and A. munroana, but differs from them by its shorter, weak and straight awn, and palea less than half the length of the lemma.